Suicidal ideation, tendencies, attempts and self-injuries in adolescents who are at risk of Internet addiction and who are addicted to the mobile phone - Potembska, Emilia (Current Problems of Psychiatry, 2012)
The aim of the work was the verification of the hypothesis assuming that adolescents who are at risk of Internet addiction and mobile phone addiction more often report suicidal ideation, plan suicide, attempt suicide and self-injure as compared to the adolescents who are not at risk of these behavioural addictions. Material and methods. The group consisting of 291 junior high school students and high school students (188 girls and 103 boys) was examined using the Questionnaire designed by the authors, the Internet Addiction Test by Young and Mobile Phone Addiction Assessment Questionnaire by Potembska and Pawłowska. Results and conclusions. Based on the obtained results the following conclusions were formulated: • Significantly more adolescents at risk of Internet addiction thought of committing suicide or planned suicide as compared to those were not at risk of Internet addiction • Significantly more adolescents at risk of Internet addiction self-injure as compared to those adolescents who are not at risk of Internet addiction. • Significantly more adolescents at risk of mobile phone addiction showed suicidal ideation and planned suicide as compared to those adolescents who are not at risk of this addiction. • Significantly more adolescents at risk of mobile phone addiction carried out self-harm as compared to those adolescents who are not at risk of this addiction.